Effect of aggregate gradation on the stiffness of asphalt mixtures - Al-Mosawe, Hasan; Thom, Nick; Airey, Gordon; Ai-Bayati, Amjad (De Gruyter Open, 2015)
Aggregate gradation plays an important role in the behaviour of asphalt mixtures. Packing of aggregate is a very important factor that will be affected by changing the aggregate gradation. Many researchers have investigated different ways of describing packing both theoretically and practically. Bailey ratios have recently been used to understand the volumetric properties of mixtures. In this paper, the Bailey ratios have been used, and two further ratios have also been introduced to allow the asphalt mixture gradation to be fully understood. Thirteen different aggregate gradations have been chosen within the 14 mm asphalt concrete specification to investigate the effect of particle size distribution on the stiffness of the mixture. It was found that variation in aggregate gradation has a significant effect on asphalt stiffness, even within specification limits, and a reasonable correlation between the set of ratios investigated and the Indirect Tensile Stiffness.